DeRisking coffee in Vietnem: Piloting a Coffee Climate Protection Insurance scheme to enhance the capacity of smallholders and agribusinesses in coping with climate variability and change - Barlis, Angelica; Swaans, Cornelis P.M.; Kath, Jarrod; Mushtaq, Shahbaz; Deniau, Aline (InsuResilience Secretariat, 2022)
While the Central Highlands in Vietnam are the largest production hub for coffee in the country and the largest Robusta coffee producer in the world, the region remains the second poorest region in the country. This makes it even more difficult for local smallholder farmers to build resilience against the increasing impacts of climate change. With the aim of reducing their vulnerability, the Alliance of Biodiversity International and CIAT together with partner organizations is piloting a Coffee Climate Protection Insurance (CCPI) scheme to enhance the capacity of smallholders and agribusinesses to cope with climate variability and change. The scheme incorporates the use of forecasts into agro-advisories, and an integrated index insurance approach for drought, excessive rainfall and temperature for coffee farmers to reduce risks and encourage good farm-management practices.